Association between adherence to the MIND diet and overweight and obesity in children: An exploratory study. (October 2022) - Asgari, Elaheh; Chamary, Maryam; Bellissimo, Nick; Azadbakht, Leila
Summary: Background & aims: Childhood obesity is concerning as it is highly prevalent worldwide and has long-term health implications in adulthood. Recently, the MIND diet was created to encourage a brain-healthy diet and focuses on plant-based eating. The relationship between the MIND diet and childhood obesity is not well understood. The objective of this study was to evaluate the association between adherence to the MIND diet and overweight and obesity in children. Methods: Data from a population-based cross-sectional study (n = 788 children aged 6 years) in Tehran, Iran was used. A 168-item semi-quantitative food frequency questionnaire was used to evaluate dietary intake. The MIND diet scores were calculated and anthropometric measurements were completed for all children. Odds ratios and 95% confidence intervals (CI) for overweight and obesity across tertiles of MIND diet scores were estimated using logistic regression analyses, adjusted for energy intake, socioeconomic status, and physical activity. Results: The mean weight, height, BMI, and total energy intake of participants were 20.85 + 2.35 kg, 113.75 + 2.00 cm, 16.12 + 1.84 kg/m 2, and 1014.74 + 259.16 (kcal/d), respectively. There was an inverse association between the MIND diet score and overweight (OR = 0.0.55, 95% CI: 0.38–0.81; P-trend = 0.002) and overweight/obesity (OR = 0.59, 95% CI: 0.41–0.86; P-trend = 0.006). Conclusions: Higher adherence to the MIND diet may lower the risk of overweight and overweight/obesity in children. Future studies using prospective study designs are needed to confirm these findings. Graphical abstract: Image 1